Employees as key resources and activities of tour and travel business model canvas - Desloehal Djumrianti; Afrizawati Afrizawati; Hendra Sastrawinata; Dinda Yuniarti Akmil Putri; Abel Apista; Youland Dwi Putri (Goodwood Publishing, 2025)
Purpose: The research aims to provide insights on how to optimize employees' contributions as indispensable using the tourism business model, helping companies better strategize and innovate their key resources and activities. Methodology/approach: The study, conducted in Palembang, used semi-structured interviews, document analysis, and focus group discussions. Nine tour and travel agencies were selected from 110 ASITA members using Slovin's formula. Data were analyzed using the Miles and Huberman model. Results/findings: The study identified key failures in tour and travel companies, including poor Human Resource Management (18%), inadequate role definition (17%), insufficient investment in employee development (13%), lack of strategic HR policies (14%), balancing cost and employee experience (11%), poor communication and support systems (15%), and external competition and workload stress (12%). Additionally, factors such as lack of knowledge, skills, experience, creativity, and commitment contributed. The study concluded that employees play a crucial role in the success of tour and travel agencies. Conclusion: The study found that recognizing employees as the most valuable asset in the tour and travel industry is essential. Their roles not only significantly influence the success of the business but also highlight that human resources are the key element in this sector. Limitations: Due to time and cost constraints, only 8.1% of ASITA members responded to this study; all were general travel agencies, with only one Hajj and Umrah company. Future studies will investigate all tour and travel agencies that are members of ASITA in South Sumatra. Contribution: This study will specifically assist tour and travel agents in Palembang to enhance their businesses by leveraging employees as key resources and activities.